Effect of Heat Treatment on Microstructural Evolution and Tribological Characteristic of a Laser Melting Deposited 12CrNi2V Low‐Alloy Steel. Issue 8 (14th May 2020) - Tang, Xu; Zhang, Song; Cui, Xue; Zhang, Chunhua; Liu, Yu; Zhang, Jingbo
Abstract : The microstructural evolution and tribological characteristics of a laser additive manufactured 12CrNi2V steel heat‐treated with four conditions are thoroughly studied to provide beneficial guidance to the prospective application of additive manufactured Cr–Ni–V steels. First, the four conditions of heat treatments are identified via a differential scanning calorimeter test. Subsequently, scanning electron microscopy, X‐ray diffraction, and electron backscattering diffraction are performed to characterize the morphologies, phase composition, and crystallographic textures of the experimental specimens. The microhardness and tribology tests are then conducted. Experimental results illustrate that the homogeneity of the microstructure is a significant factor in determining the tribological characteristic, which is mainly controlled by the type and distribution of the carbides. The heat treatments adopted in this work can remarkably modify the laser‐induced microstructural inhomogeneity, thereby promoting the tribological characteristic of the steel. Furthermore, the specimen tempered at 620 °C demonstrates an excellent combination of microhardness and toughness. Therefore, it is concluded that 620 °C is the optimal tempering temperature for the laser additive manufactured 12CrNi2V steel. Abstract : In view of the extensive application of laser melting deposited 12CrNi2V low‐alloy steel, the heterogeneous microstructure caused by the thermal effect is alleviated through heat treatments in this research, thereby improving the basic tribological characteristics. The optimum heat treatment regime is determined by a combined analysis of microstructure, microhardness, and wear mechanism.